Fumigant toxicity of eugenol and its negative effects on biological development of Callosobruchus maculatus L - González-Armijos, Maria José; Viteri Jumbo, Luis; Faroni, Lêda Rita; Oliveira, Eugenio Eduardo; Flores, Adolfo Fernando; Heleno, Fernanda; Haddi, Khalid (Revista de Ciencias Agrícolas, 2019)
The protection of stored products from insect damages, when accomplished, is mostly relying on the application of synthetic insecticides with serious health and environmental issues in addition to risks of selection of resistant insect populations associated with such practice. The use of plants derived compounds have been presented as sound strategy for sustainable insect pest management. Eugenol is an aromatic component of natural occurrence in essential oils of numerous plants. known for its repellent and insecticidal bioactivities against different insect species. Here, we investigated the fumigant application of eugenol to control the cowpea weevil Callosobruchus maculatus (Coleoptera: Chrysomelidae: Bruchinae) by assessing toxicity, effects on biological development (including emergence inhibition) and repellency to these weevil. Besides a good fumigant insecticidal activity, eugenol exposure resulted in a dose-dependent decrease of the growth rate of C. maculatus associated with a steady reduction in bean mass losses. Additionally, inhibition of offspring was upper 50% when adults were exposed to lethal and sublethal concentrations. significant inhibition of the offspring emergence was achieved after the exposure of parental adults to lethal and sublethal doses of eugenol. Furthermore, adult weevils were repelled away from beans exposed to high dose (LD99) of eugenol in contrast with their attraction to the beans treated with lower dose (LD50). Our findings suggest that eugenol has potential as control tool to be used in sustainable management startegies of C. maculatus.